Millennials and Z's Intention to Leave: Leadership, Work Environment, Workload, Flexible Work, Job Satisfaction - Pertiwi, Ni Made Marlynia Sukma; Prena, Gine Das (Jurnal Aplikasi Manajemen, 2024)
Intention to leave from millennial and z generation employees in the company is quite high. This will cause problems for the company's sustainability in the future. This research was conducted in the retail industry of WHSmith Indonesia which is spread across 3 regions of Bali, Jakarta and Makassar, which aims to investigate the factors that influence employee intention to leave, there are transformational leadership, work environment, workload, and flexible work arrangement using job satisfaction as a mediating variable. In this study using 168 millennial and z generation employees in WHSmith who participated in filling out questionnaires using SEM-PLS and uses a millennial and z generation multigroup test with the SmartPLS 4 analysis tool. The results showed that transformational leadership and work environment had no effect on intention to leave, workload had a positive effect on intention to leave, meanwhile flexible work arrangement and job satisfaction had a negative effect on intention to leave, transformational leadership, work environment, and flexible work arrangement have a positive effect on job satisfaction, meanwhile workload has a negative effect on job satisfaction, transformational leadership, work environment, and flexible work arrangement have a negative effect on intention to leave through job satisfaction as a mediating variable, meanwhile workload has a positive effect on intention to leave through job satisfaction as a mediating variable among WHSmith employees. The results of multigroup analysis are also discussed in this study. This research provide insight for the WHSmith company regarding the causes of intention to leave in the millennials and z generations, so the company can have loyal employees in the future.